2021
DOI: 10.2334/josnusd.20-0444
|View full text |Cite
|
Sign up to set email alerts
|

Influence of preformed bone defects on key pathogens and bone loss during experimental peri-implantitis formation in a canine model

Abstract: Purpose: To determine the impact of experimentally preformed periimplant crater-shaped bone defects on the evolution of in situ microbiota and development of bone defects compared to those induced over time by ligature placement only. Methods: Implants were installed in the mandibles of eight dogs. Standardized bone defects were preformed in four test animals but not in the other four control animals, prior to implant (3.3 mm × 8 mm) installation. After 2 months of healing, peri-implantitis was induced with si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Despite similarities regarding the composition of the bacterial biofilms [ 1 ], there are differences in the extent of tissue destruction between peri-implantitis and periodontitis. A peri-implantary bone destruction progresses more rapidly and is usually characterized by crater-shaped bony defects around the implant, which could be explained by the lack of periodontal tissue structures, such as Sharpey's fibers [ 2 ]. In addition, it has been reported that peri-implant tissues show reduced vascularization characteristics [ 3 ], which might restrict the healing processes of the peri-implant tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Despite similarities regarding the composition of the bacterial biofilms [ 1 ], there are differences in the extent of tissue destruction between peri-implantitis and periodontitis. A peri-implantary bone destruction progresses more rapidly and is usually characterized by crater-shaped bony defects around the implant, which could be explained by the lack of periodontal tissue structures, such as Sharpey's fibers [ 2 ]. In addition, it has been reported that peri-implant tissues show reduced vascularization characteristics [ 3 ], which might restrict the healing processes of the peri-implant tissue.…”
Section: Introductionmentioning
confidence: 99%